2016
DOI: 10.1111/bjh.13927
|View full text |Cite
|
Sign up to set email alerts
|

A CD138‐independent strategy to detect minimal residual disease and circulating tumour cells in multiple myeloma

Abstract: CD138 (also termed SDC1) has been the gold-standard surface marker to detect multiple myeloma (MM) cells for decades; however, drug-resistant residual and circulating MM cells were shown to have lower expression of this marker. In this study, we have shown that residual MM cells following bortezomib treatment are hypoxic. This combination of drug exposure and hypoxia down-regulates their CD138 expression, thereby making this marker unsuitable for detecting residual or other hypoxic MM cells, such as circulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 51 publications
0
20
0
2
Order By: Relevance
“…We also studied the effects of different factors (such as hypoxia or co-culture with stroma) on the expression of CD47 in MM cells. Both hypoxia and stroma were previously shown to change the expression of MM surface biomarkers and sensitivity to therapy [29,36,37]. We found that neither of these had an effect on CD47 expression.…”
Section: Discussionmentioning
confidence: 56%
“…We also studied the effects of different factors (such as hypoxia or co-culture with stroma) on the expression of CD47 in MM cells. Both hypoxia and stroma were previously shown to change the expression of MM surface biomarkers and sensitivity to therapy [29,36,37]. We found that neither of these had an effect on CD47 expression.…”
Section: Discussionmentioning
confidence: 56%
“…Low oxygenation (hypoxia) in the BM microenvironment was shown to occur beyond physiologic BM conditions during the progression of MM and, together with cellular and acellular components, plays a critical role in MM dissemination, stem cell–like properties, and drug resistance [27], [30], [39]. Our research group reported enhanced MM drug resistance to current therapies, including bortezomib and carfilzomib, in hypoxic MM cells [27], [40]. Therefore, targeting hypoxic cells to abolish the drug-resistant cancer population is the vital goal to prevent recurrence in MM patients.…”
Section: Discussionmentioning
confidence: 90%
“…The characterization of MM by a single surface marker is being questioned over the last decade. CD138, the gold standard surface marker to detect MM cells, is shown to be affected by drug exposure and hypoxia . Other secondary antibodies used in combinations such as CD38, CS1, and CD20 are highly expressed in many other cell types .…”
Section: Future Directionsmentioning
confidence: 99%
“…The EPR effect is an important factor for delivery of nanoparticle systems in general, which has been confirmed mainly for solid tumors. 110 Other secondary antibodies used in combinations such as CD38, CS1, and CD20 are highly expressed in many other cell types. 111 Other markers such as VLA4-4 is expressed in several cell types, and the expression in MM cells is very heterogeneous.…”
Section: Challenges Of Nps For MM Treatmentmentioning
confidence: 99%